Simulation Of High Voltage Gain Boost Converter For Battery Charging With PV System In A Single Stage Conversion (International Journal of Engineering and Computer Science, 2018)
The require for renewable energy sources is on the rise because of the sensitive energy crisis in the world today. Renewable energy is the energy which comes from natural resources such as sunlight, wind, rain, tides and geothermal heat. These resources are renewable and can be obviously replenished. Therefore, for all practical purposes, these resources can be considered to be never-ending, unlike diminishing conventional fossil fuels. In order to give support to the growing technology demand of renewable energy applications. This work presents a high voltage gain boost converter topology based on battery charging using coupled inductors and solar panels to decrease ripples in output voltage. The presented converter operates in Zero voltage switching (ZVS) mode for all switches. By using the novel concept of single –stage approaches, the converter be capable of generate a dc bus simultaneous charge of the batteries according to the radiation level. In this paper we can check the output voltage ripple in various MPPT techniques. Simulation is done by using the MATLAB/SIMULINK.